2008
DOI: 10.1002/jso.21054
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement on the loco‐regional treatment of appendiceal mucinous neoplasms with peritoneal dissemination (pseudomyxoma peritonei)

Abstract: Pseudomyxoma peritonei (PMP) is a rare condition mostly originating from low malignant potential mucinous tumours of the appendix. Although this disease process is minimally invasive and rarely causes haematogenous or lymphatic metastases, expectation of long-term survival are limited with no prospect of cure. Recently, the combined approach of cytoreductive surgery (CRS) and perioperative loco-regional chemotherapy (PLC) has been proposed as the standard of treatment for the disease. The present paper summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(123 citation statements)
references
References 46 publications
3
108
0
12
Order By: Relevance
“…One of the most important factors is attaining complete cytoreduction, which is achieved in 40-91% of cases. 87,88 In one study, patients who had complete cytoreduction had a 5-and a 10-year survival rate of 87% and 74%, respectively, whereas those in which complete cytoreduction could not be achieved had 34% and 23% 5-and 10-year survival rates. 87 In this regard, the experience of the surgeon may have a role, with specialized centers achieving better survival statistics.…”
Section: Treatmentmentioning
confidence: 99%
“…One of the most important factors is attaining complete cytoreduction, which is achieved in 40-91% of cases. 87,88 In one study, patients who had complete cytoreduction had a 5-and a 10-year survival rate of 87% and 74%, respectively, whereas those in which complete cytoreduction could not be achieved had 34% and 23% 5-and 10-year survival rates. 87 In this regard, the experience of the surgeon may have a role, with specialized centers achieving better survival statistics.…”
Section: Treatmentmentioning
confidence: 99%
“…In a multicenter study on 2296 patients treated with CRS and HIPEC, the median survival has been reported as 196 months, and 10-year overall survival rate as 63% (63). In the same study, the mean (64). Pseudomyxoma peritonei is the disease with the best response to this treatment regardless of the PCI score.…”
Section: Discussionmentioning
confidence: 90%
“…Results are encouraging with a 5-ys-OS ranging from 62.5 to 100% for low grade PMP and from 0 to 65% for high grade disease . This differentiation is crucial for the evolution of disease; low grade tumours are slow growing and indolent differently from those high grade, fast growing and aggressive (Sugarbaker and Chang, 1999;Witkamp et al, 2001;Güner et al, 2005;Moran et al, 2008;Moran and Cecil, 2003;Murphy et al, 2007;Baratti et al, 2008;Elias et al, 2008;Loungnarath et al, 2005;Smeenk et al, 2007;Stewart et al, 2005;Yan et al, 2006). The goal of the surgical cytoreduction is to remove all the visible tumor by the following procedures: right subdiaphragmatic and parietal peritonectomy, left subdiaphragmatic and parietal peritonectomy,greater omentectomy with splenectomy, lesser omentectomy and stripping of the omental bursa, andpelvic peritonectomy with salpingo-oophorectomy in women.…”
Section: Advanced Oncological Surgery In Pseudomyxoma Peritoneimentioning
confidence: 99%